2023
DOI: 10.1111/geb.13718
|View full text |Cite
|
Sign up to set email alerts
|

The geographic range size and vulnerability to extinction of angiosperm epiphytes in the Atlantic Forest of Brazil

Abstract: AimAngiosperm epiphytes have long been reported to have larger geographic ranges than terrestrial species, despite evidence of their outstanding diversity and endemism. This apparent contradiction calls for further investigation of epiphytes' poorly understood range size patterns. Here, we address the question of whether epiphytes have larger geographic ranges and different vulnerability to extinction than terrestrial species.LocationThe Atlantic Forest of Brazil, a global centre of tropical epiphyte diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
1
1
0
Order By: Relevance
“…We found support for known spatial hotspots of extinction risk such as Madagascar and Hawaii. We found that epiphytes are highly threatened, with an elevated extinction risk of 53.9% (95% CI 52 – 56%, compared to the current Red List 49%), which is consistent with findings that 45% of epiphytes have a high proportion of species with ‘vulnerably small ranges’ compared to other life forms (Leão et al ., 2023). For large families (>= 3,000 species) the estimations of percentage threatened are broadly similar for the Red List and our predictions (Figure 1).…”
Section: Discussionsupporting
confidence: 91%
“…We found support for known spatial hotspots of extinction risk such as Madagascar and Hawaii. We found that epiphytes are highly threatened, with an elevated extinction risk of 53.9% (95% CI 52 – 56%, compared to the current Red List 49%), which is consistent with findings that 45% of epiphytes have a high proportion of species with ‘vulnerably small ranges’ compared to other life forms (Leão et al ., 2023). For large families (>= 3,000 species) the estimations of percentage threatened are broadly similar for the Red List and our predictions (Figure 1).…”
Section: Discussionsupporting
confidence: 91%
“…We found support for known spatial hotspots of extinction risk such as Madagascar and Hawaii. We found that epiphytes are highly threatened, with an elevated extinction risk of 53.9% (95% CI 52–56%, compared to the current Red List 49%), which is consistent with findings that epiphytes have a high proportion of species with ‘vulnerably small ranges’ (Leão et al ., 2023; Svahnström et al ., 2023). For large families (≥ 3000 species), the estimations of percentage threatened are broadly similar for the Red List and our predictions (Fig.…”
Section: Discussionmentioning
confidence: 99%